Rapid typing of Klebsiella pneumoniae and Pseudomonas aeruginosa by Fourier-transform Infrared spectroscopy informs infection control in veterinary settings - Zendri, Flavia; Schmidt, Vanessa; Mauder, Norman; Loeffler, Anette; Jepson, Rosanne Ellen; Isgren, Cajsa; Pinchbeck, Gina; Haldenby, Sam; Timofte, Dorina (Frontiers in Microbiology, 2024)
The emergence of multi-drug resistant (MDR) pathogens linked to healthcareassociated infections (HCAIs) is an increasing concern in modern veterinary practice. Thus, rapid bacterial typing for real-time tracking of MDR hospital dissemination is still much needed to inform best infection control practices in a clinically relevant timeframe. To this end, the IR Biotyper using Fourier-Transform InfraRed (FTIR) spectroscopy has the potential to provide fast cluster analysis of potentially related organisms with substantial cost and turnaround time benefits. Materials & Methods: A collection of MDR bacterial isolates (n= 199, comprising 92 Klebsiella pneumoniae and 107 Pseudomonas aeruginosa) obtained from companion animal (i.e. dogs, cats and horses) clinical investigations, faecal and environmental screening from four veterinary facilities between 2012 and 2019 was analysed retrospectively by FTIR spectroscopy. Its performance was compared against MLST extracted from whole genomes of a subset of clustering isolates (proportionally to cluster size) for investigation of potential nosocomial transmission between patients and the surrounding hospital environments.Results: Concordance between the FTIR and MLST types was overall high for K. pneumoniae (Adjusted Rand Index [ARI] of 0.958) and poor for P. aeruginosa (ARI of 0.313). FTIR K. pneumoniae clusters (n=7) accurately segregated into their respective veterinary facility with evidence of intrahospital spread of K. pneumoniae between patients and environmental surfaces. Notably, K. pneumoniae ST147 intensely circulated at one Small Animal Hospital ICU. Conversely, Pseudomonas aeruginosa FTIR clusters (n=18) commonly contained isolates of diversified hospital source and heterogeneous genetic background (as also genetically related isolates spread across different clusters); nonetheless, dissemination of some clones, such as P. aeruginosa ST2644 in the equine hospital, was apparent. Importantly, FTIR clustering of clinical, colonisation and/or environmental isolates sharing genomically similar backgrounds was seen for both MDR organisms, highlighting likely crosscontamination events that led to clonal dissemination within settings.Conclusions: FTIR spectroscopy has high discriminatory power for hospital epidemiological surveillance of veterinary K. pneumoniae and could provide sufficient information to support early detection of clonal dissemination, facilitating implementation of appropriate infection control measures. Further work and careful optimisation need to be carried out to improve its performance for typing of P. aeruginosa veterinary isolates.